2024
DOI: 10.3389/fimmu.2024.1346686
|View full text |Cite
|
Sign up to set email alerts
|

Epacadostat stabilizes the apo-form of IDO1 and signals a pro-tumorigenic pathway in human ovarian cancer cells

Sofia Rossini,
Sara Ambrosino,
Claudia Volpi
et al.

Abstract: The tryptophan-degrading enzyme indoleamine 2,3-dioxygenase 1 (IDO1) is a plastic immune checkpoint molecule that potently orchestrates immune responses within the tumor microenvironment (TME). As a heme-containing protein, IDO1 catalyzes the conversion of the essential amino acid tryptophan into immunoactive metabolites, called kynurenines. By depleting tryptophan and enriching the TME with kynurenines, IDO1 catalytic activity shapes an immunosuppressive TME. Accordingly, the inducible or constitutive IDO1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…In view of these findings, we can infer that IDO plays an important role in the complex interplay of postoperative immunomodulation after cardiac surgery. This is interesting, as IDO can be selectively targeted and inhibited [ 3 , 4 , 30 , 31 , 32 ], and therefore a therapeutic intervention might potentially mitigate postoperative complications. Nevertheless, we were not able to associate perioperative metabolite dynamics with clinical outcome measures in an exploratory analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of these findings, we can infer that IDO plays an important role in the complex interplay of postoperative immunomodulation after cardiac surgery. This is interesting, as IDO can be selectively targeted and inhibited [ 3 , 4 , 30 , 31 , 32 ], and therefore a therapeutic intervention might potentially mitigate postoperative complications. Nevertheless, we were not able to associate perioperative metabolite dynamics with clinical outcome measures in an exploratory analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This immune response is fueled by multiple factors such as the surgical trauma itself, blood interaction with extracorporeal circuits, and reperfusion injury [ 27 ], and has repeatedly been shown to influence postoperative outcomes [ 27 , 28 , 29 ]. IDO’s involvement in inflammatory responses and in conditions associated with heightened immune activation, such as CPB surgery, might serve as an immune marker and potential therapeutic target [ 3 , 4 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then taking advantage of already-elevated MAPK levels in drugresistant ovarian cancer cells, elaiophylin overcame resistance to chemotherapy in ovarian cancer. Furthermore, very recently, Rossini et al (142) demonstrated that tyrosine phosphorylation and the association of indoleamine 2,3-dioxygenase 1 (IDO1) with SHP2 were significantly increased in SKOV-3 cells in response to the IDO1-inhibitor and -stabilizer epacadostat. Meanwhile, in SKOV-3 cells treated with epacadostat the signaling triggered by the transducing molecular complex IDO1-SHP2 accelerates the migratory capacity and the colony-forming ability of SKOV-3 cells, suggesting a pro-tumorigenic phenotype.…”
Section: Ovarian Cancermentioning
confidence: 99%